Nancy Love and the WASP ferry pilots of World War II - Rickman, Sarah Byrn (North Texas military biography and memoir series ;, 2008)
She flew the swift P-51 and the capricious P-38, but the heavy, four-engine B-17 bomber and C-54 transport were her forte. This is the story of Nancy Harkness Love who, early in World War II, recruited and led the first group of twenty-eight women to fly military aircraft for the US Army.